The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1968
DOI: 10.1111/j.1476-5381.1968.tb07062.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of drugs on the constriction of isolated depolarized blood vessels in response to calcium or barium

Abstract: 1. The rat isolated anterior mesenteric artery was perfused at a constant rate with a calcium-free depolarizing solution. Injection close to the cannula of 0.05-0.1 ml. of solutions of CaCI2 (117 mM) or BaCl2 (100 mM) caused a rise in perfusion pressure.2. The responses to injected CaClI solution could be obtained repeatedly but those to successive injections of BaCl2 solution slowly declined. When the responsiveness to barium had almost disappeared, it could be restored by the addition to the perfusing fluid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

1969
1969
1978
1978

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 33 publications
2
19
0
Order By: Relevance
“…The evidence of Northover (1968) coupled with the restorative action of prostaglandins is suggestive of prostaglandin participation in calcium activation of vascular smooth muscle contraction in rat mesenteric blood vessels. Any interpretation should however, be regarded with caution in view of the multiple effects of indomethacin and other NSAIDs.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…The evidence of Northover (1968) coupled with the restorative action of prostaglandins is suggestive of prostaglandin participation in calcium activation of vascular smooth muscle contraction in rat mesenteric blood vessels. Any interpretation should however, be regarded with caution in view of the multiple effects of indomethacin and other NSAIDs.…”
Section: Discussionmentioning
confidence: 95%
“…Apart from the non-specific actions of indometha-cin already mentioned, Northover (1968; demonstrated that vasoconstrictor responses of the rat isolated perfused anterior mesenteric artery to adrenaline and to calcium ions were prevented or abolished by indomethacin and other NSAIDs. Continued perfusion of the tissue with calcium-containing depolarizing solution (high K+) caused a persistent rise in perfusion pressure which was rapidly reversed by these agents.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the accumulation of small amounts of ionic calcium within the cytoplasm of muscle cells is required to trigger the shortening of the contractile proteins (Somlyo & Somlyo, 1968. It may be significant, therefore, that indomethacin and a group of pharmacologically related drugs which are used clinically to treat various forms of tissue injury also inhibit contraction of smooth muscle in response to a variety of spasmogenic agents (Northover, 1967a(Northover, , b, 1968 and this inhibitory action can be attributed to the prevention of the net gain of calcium by the muscle cells (Northover, 1971). The experiments to be reported here were designed to investigate whether, in electrically stimulated smooth muscle, indomethacin prevents the net fluxes of other cations besides calcium, and were extended to include similar observations on certain other tissues.…”
Section: Introductionmentioning
confidence: 99%